2007
DOI: 10.1590/s0004-282x2007000200012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the signs and symptoms of temporomandibular disorders in children with headaches

Abstract: There is a higher frequency of TMD in pediatric patients with headaches; thus, it is important to look for TMD signs and symptoms in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 13 publications
6
25
0
2
Order By: Relevance
“…However, this relationship has not always been investigated or described (19) and some studies have only cited age as exerting an influence on the association between these clinical conditions (20,21). Nevertheless, a recent large study by Tecco et al reported a significant association between TMD/headache and patient characteristics, such as female gender, young age, and the presence of posterior unilateral crossbite (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, this relationship has not always been investigated or described (19) and some studies have only cited age as exerting an influence on the association between these clinical conditions (20,21). Nevertheless, a recent large study by Tecco et al reported a significant association between TMD/headache and patient characteristics, such as female gender, young age, and the presence of posterior unilateral crossbite (22).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Moreover, signs and symptoms of TMD occur more often in adolescents with HA in comparison with those who are HA-free. 17 Indeed, there is a lack of studies in large population samples, and in most cases, TMD pain characteristics have not been explored in depth with regard to this association. Thus, the aim of the present study was to verify whether HAs are associated with TMD diagnosis and pain characteristics, using standardized methods of sampling and data collection in young adolescents.…”
mentioning
confidence: 99%
“…A higher number of TMD signals and symptoms is found in children with headache 20 , with association between moderate and severe TMD and primary headaches in a population 21 of children and adolescents, but some findings in adult population cannot be easily compared due to a great number of nomenclatures and different analyses.…”
Section: Discussionmentioning
confidence: 99%